Funcionários públicos e flexibilidade gerencial: Uma experiência brasileira - Valdir Melo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The history of the DASP (now extinct) and of the civil service reform in the 1930s shows that as a matter of fact the supposed merit system lacked strength. That is, a large share of the civil servants kept being selected by means of favoritism. Afterwards, in the years up to 1988, favoritism prevailed in spite of several changes in the pertinent legislation. This text has reflections on the issue, as well as it deals with words and concepts that help understanding the matter. It presents some important usages and institutions of favoritism. Besides, it reports the continuity of favoritism throughout several stages of Brazilian political history. This information may be of benefit to rethinking institutional changes that strengthen and improve the merit system.
Keywords: D73; A13; B40; 330; civil servant; public official; political partisan favoritism; managerial flexibility; civil service reforms